Success rate of pulpal anesthesia with supplemental intraligamentary injection after failure of inferior alveolar nerve block in young permanent teeth - Thitida Sutharaphan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Aim: The purposes of this study were threefold. First was to study the success of pulpal anesthesia with inferior alveolar nerve block (IANB) in young permanent teeth with deep caries diagnosed as normal pulp, reversible pulpitis, and irreversible pulpitis. Second was to study the success rate of pulpal anesthesia with supplemental intraligamentary injection (IL) after the failure of IANB. And the final purpose was to compare the success rates of pulpal anesthesia between young permanent teeth diagnosed as normal pulp, reversible pulpitis, and irreversible pulpitis. Methods: The anesthetic agent used in all steps of this study was 4% articaine with epinephrine 1:100,000. Sixty young permanent teeth, from patients aged between 7-20 years, with deep caries diagnosed as normal pulp, reversible pulpitis, and irreversible pulpitis were anesthetized with IANB. When the failure of pulpal anesthesia with IANB occurred, IL was supplementary administered. Both pre-operative and intra-operative pulpal anesthesias were assessed. Success of pre-operative pulpal anesthesia was defined as no response to both the Endo-Ice® cold test and electric pulp tests. Success of intra-operative pulpal anesthesia was determined by the Wong-Baker faces pain rating scale (WBFPS). Results: The pre-operative pulpal anesthetic success of IANB was 26.67% (16/60). In 44 patients who had IANB failures, IL was administered and the pre-operative cumulative success rate of pulpal anesthesia by IL was 80% (48/60). Intra-operatively, 68.75% (11/16) and 75% (24/32) of patients who had pre-operative pulpal anesthetic success of IANB and IL had pulpal anesthetic success during treatment. There was no significant difference of pulpal anesthetic successes between the different diagnosis groups. Conclusion: The pulpal anesthetic success of IANB in young permanent teeth with deep caries diagnosed as normal pulp, reversible pulpitis, and irreversible pulpitis was quite low. The supplementary injection, such as IL injection, is highly recommended to effectively enhance the pulpal anesthetic success rate in this group of teeth.